2014
DOI: 10.1128/jvi.00774-14
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine/Chemokine Responses in Activated CD4+and CD8+T Cells Isolated from Peripheral Blood, Bone Marrow, and Axillary Lymph Nodes during Acute Simian Immunodeficiency Virus Infection

Abstract: Understanding the cytokine/chemokine networks in CD4؉ and CD8 ؉ T cells during the acute phase of infection is crucial to design therapies for the control of early human immunodeficiency virus ( ؉ and CD8 ؉ T cells, upregulation of ␤-chemokines, fibroblast growth factor-basic, hepatocyte growth factor, and migration inhibition factor may provide a poor prognosis. and CD8 ؉ T cells, upregulation of ␤-chemokines (CCL2 and CCL22), basic fibroblast growth factor (FGF-basic), hepatocyte growth factor (HGF), and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 72 publications
1
25
0
Order By: Relevance
“…In vitro stimulation of human (Krakauer, 1999; Sperber et al, 1995) and non-human primate (Kenway-Lynch et al, 2014) leukocytes by SEB induces an array of cytokine and/or chemokine release, as in vivo exposure of non-human primates to this toxin does (Komisar et al, 2001; Weng et al, 1997). Studies using piglet models of SEB toxicity have also shown the rapid and dramatic induction of numerous cytokines (Hudson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro stimulation of human (Krakauer, 1999; Sperber et al, 1995) and non-human primate (Kenway-Lynch et al, 2014) leukocytes by SEB induces an array of cytokine and/or chemokine release, as in vivo exposure of non-human primates to this toxin does (Komisar et al, 2001; Weng et al, 1997). Studies using piglet models of SEB toxicity have also shown the rapid and dramatic induction of numerous cytokines (Hudson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently believed that we may be able to cure HIV‐1 infection if viral reservoirs are eliminated. The simian immunodeficiency virus (SIV)‐infected rhesus macaque (RM) model is a well‐accepted model of AIDS and has been extremely useful in exploring viral reservoir where SIV infection causes escalating immune dysfunction by rapid and persistent depletion of both central and effector memory CD4+ T cells, and perpetual immune activation and inflammation . Here, we report an interesting case where SIV‐infected cells were in majority is non‐proliferating cells that include T cells, macrophages, and dendritic cells.…”
Section: Quantification Of Total Ki67pos and Siv Rna‐positive Prolifementioning
confidence: 99%
“…To examine cell phenotypes and cytokine production, a cytokine flow cytometry assay was used on freshly isolated samples to detect either CD3 ϩ or CD3 Ϫ lymphocytes spontaneously producing cytokines (IFN-␥, TNF-␣, and IL-10) according to the methods previously described (23,(28)(29)(30). Briefly, the intestinal IE and LP lymphocytes were resuspended at 10 6 cells/100 l, stained with aqua fluorescent reactive Live/Dead stain kit (Life Technologies), and surface stained with directly conjugated MAbs to CD3, CD4, and/or CD45 (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%